Knowledge, Attitudes, and Practices Toward Typhoid Fever Prevention Among Islamic Boarding School Students: A Cross-Sectional Study in Bandar Lampung, Indonesia: Sutarto, Nanda Frisila Rajagukguk, Nanda Fitri Wardani, dan Indri Windarti - sutarto sutarto; Nanda Frisila Rajagukguk; Nanda Fitri Wardani; Indri Windarti (Jurnal Kedokteran Universitas Lampung, 2026)
Typhoid fever remains a major public health concern in developing countries, including Indonesia, particularly in communities characterized by inadequate sanitation and high population density, such as Islamic boarding schools. Knowledge, attitudes, and practices (KAP) play a crucial role in preventing infectious diseases, including typhoid fever. This study aimed to determine the relationship between knowledge and attitudes and typhoid fever prevention practices among students of Madarijul Ulum Islamic Boarding School in Bandar Lampung, Indonesia. An analytic observational study with a cross-sectional design was conducted involving 142 students selected through proportionate stratified random sampling. Data were collected using a structured questionnaire assessing respondents’ knowledge, attitudes, and preventive practices regarding typhoid fever. The instrument had been tested for validity and reliability prior to data collection. Data were analyzed using univariate and bivariate analyses, with the Chi-square test applied to examine associations between variables at a 95% confidence level. The results showed that 51.4% of respondents had poor knowledge, 59.9% demonstrated positive attitudes, and 62.0% exhibited inadequate typhoid fever prevention practices. Significant associations were found between knowledge and preventive practices (p=0.007; OR=2.57) and between attitudes and preventive practices (p=0.007; OR=2.27). Students with better knowledge and more positive attitudes were more likely to engage in appropriate typhoid fever prevention practices. In conclusion, knowledge and attitudes were significantly associated with typhoid fever prevention practices among Islamic boarding school students. Strengthening health education and promoting positive health behaviors are essential to improving disease prevention efforts and reducing the risk of typhoid fever transmission in boarding school settings.